Characteristic pollutants and microbial community in underlying soils for evaluating landfill leakage. (1st January 2023) - He, Ruo; Peng, Chun; Jiang, Lei; Han, Hua; Chu, Yi-Xuan; Wang, Jing; Liu, Chen-Yang; Zhao, Nannan
Graphical abstract: Highlights: NO3 − -N, NO2 − -N, NH4 + -N, OM, TN, EC and Cl − showed a leaching dynamic along depths. Cl − was significantly positively correlated with TN, NH4 + -N, OM, NO3 − -N and EC. TN, NH4 + -N, OM, NO3 − -N, and EC were used as characteristic pollutants. NO3 − -N, NH4 + -N, NO2 − -N, SO4 2−, pH and EC greatly affected microbial communities. Hydrogenispora and Caldicoprobacter were selected as characteristic microorganisms. Abstract: Leachate leakage poses a serious environmental risk to the safety of surrounding soils and groundwater. A much faster approach to reflect landfill leakage is the premise to mitigate the ecological risk of landfills. In this study, two landfills (BJ and WZ) were selected to investigate the leaching characteristics of various pollutants along the vadose soil depths. The physiochemical properties of underlying soils including NO3 − -N, NO2 − -N, NH4 + -N, OM, TN, EC and Cl − exhibited a typical leaching dynamic along the depths. Among them, TN, NH4 + -N, OM, NO3 − -N, and EC might be used as characteristic pollutants to evaluate the leachate leakage issues in landfilled sites. The genera Thiopseudomonas, Acinetobacter, Pseudomonas, and Hydrogenispora dominated in underlying soils. Compared to BJ samples, a more diverse and active microbiome capable of carbon and nitrogen cycles was observed in WZ samples, which was mainly ascribed to nutrients and elements contained in different types of soils. Among the environmental factors, nitrogenous compounds, SO4 2−, pH and EC had significant effects on the microbial community structures in the underlying soils. The relative abundances of Hydrogenispora and Caldicoprobacter might be used as characteristic microorganisms to evaluate the leachate leakage issues in landfilled sites. These results provided a deep insight into effects of leachate leakage in underlying soils, especially the pollutants vertical distribution and the corresponding microbial community structures.